أثر الصدمات النقدية وعدم الاستقرار المالي على ديناميكيات تمويل التجارة الخارجية في الاقتصاد الريعي - أبوغاليةد. وسام عبدالسلام (Aljameai, 2025)
المستخلص: تهدف هذه الورقة إلى تحليل وقياس أثر الإصلاحات النقدية المتلاحقة، وتحديداً سياسات "تخفيض العملة المالي" (Fiscal Devaluation)، على هيكل تمويل التجارة الخارجية (الاعتمادات المستندية) في ليبيا خلال الفترة الممتدة من 2000 إلى 2025. اعتمدت الدراسة على المنهج الوصفي التحليلي لتقييم التطورات الأخيرة، بما في ذلك فرض "ضريبة النقد الأجنبي" في 2024 والتخفيض الرسمي للدينار في أبريل 2025، والمنهج القياسي باستخدام نموذج الانحدار اللوغاريتمي المزدوج (Log-Log Model)، توصلت الدراسة إلى نتائج قياسية تعكس عمق التشوه الهيكلي؛ حيث أظهرت أن الطلب على الاعتمادات المستندية "غير مرن" سعرياً (-0.38)، مما يعني أن رفع تكلفة الدولار (سواء عبر الضريبة أو التخفيض) لم ينجح في كبح الواردات، بل تزامن عام 2025 مع طفرة في فتح الاعتمادات رغم ارتفاع السعر الرسمي إلى 5.56 دينار. في المقابل، أثبتت النتائج أن "الإنفاق الحكومي الممول بالنفط" هو المحرك المهيمن للواردات بمرونة دخلية مرتفعة (0.95)، توصي الدراسة بضرورة الانتقال من "إدارة السعر" إلى "إدارة الكمية" عبر تفعيل ميزانية موحدة وضبط الإنفاق العام، حيث أن الاعتماد المنفرد على سعر الصرف في ظل غياب السياسة المالية الرشيدة يؤدي فقط إلى تغذية التضخم التكاليفي دون تحقيق التوازن الخارجي. Abstract: This paper aims to analyze and measure the impact of successive monetary reforms, specifically fiscal devaluation policies, on the structure of foreign trade financing (letters of credit) in Libya during the period from 2000 to 2025. The study adopted the descriptive analytical approach to assess recent developments, including the imposition of the foreign exchange tax in 2024 and the official devaluation of the dinar in April 2025, and the econometric approach using the double logarithmic regression model (Log-Log Model). The study reached econometric results that reflect the depth of the structural distortion; it showed that the demand for letters of credit is price-inelastic (-0.38), which means that raising the cost of the dollar (whether through the tax or the devaluation) did not succeed in curbing imports. Rather, 2025 coincided with a surge in opening letters of credit despite the rise of the official price to 5.56 dinars. In contrast, the results proved that “oil-financed government spending” is the dominant driver of imports with a high-income elasticity (0.95). The study recommends the need to move from “price management” to “quantity management” by activating a unified budget and controlling public spending, since relying solely on the exchange rate in the absence of a sound fiscal policy only fuels cost-push inflation without achieving external balance.